Correlation among ocular surface changes and systemic hematologic indexes and disease activity in primary Sjögren’s syndrome: a cross-sectional study - Yan He; Jianing Feng; Wen Shi; Yuerong Ren; Yingyi Liu; Huanmin Kang; Jing Tian; Ying Jie (BMC Ophthalmology)
Abstract Background To explore the relationship among ocular surface changes, systemic hematologic indexes, and disease activity in primary Sjögren’s syndrome patients. Methods Thirty-three primary Sjögren’s syndrome patients and 36 healthy controls were recruited in this cross-sectional study. All participants underwent complete ocular surface testing, including dry eye symptoms and signs, tear multi-cytokine analysis, and conjunctival impression cytology (CIC). Multiple systemic hematologic indexes and disease activity were also evaluated, including autoantibodies, immune cells, the EULAR Sjögren’s Syndrome Patient Reported Index (ESSPRI), and the EULAR Sjögren’s Syndrome Disease Activity Index (ESSDAI). Results Primary Sjögren’s syndrome patients exhibited significant dry eye, severe conjunctivochalasis, decreased goblet cell density, and severe squamous epithelial on the ocular surface. Interferon-inducible T cell alpha chemoattractant (I-TAC), granulocyte-macrophage colony-stimulating factor (GM-CSF), interleukin (IL)-1β, IL-5, IL-8, IL-10, IL-13, IL-21, C-C motif chemokine ligand (CCL)4, interferon-gamma (IFN-γ), CCL20, and tumor necrosis factor-gamma (TNF-α) in the tear fluid of pSS patients changed significantly. Correlation analysis showed that anti-SSA was relevant to ocular surface disease index (OSDI) score, tear break-up time (TBUT), and meibomian gland secretion (MGS). CD8+ T cell percentages were relevant to TBUT and corneal fluorescein staining score (CFS). IL-8, IL-13, CCL4, and TNF-α were correlated with RF-IgA. IL-1β, CCL4, and TNF-α were correlated with CD8+ T cell counts. IL-5 and CCL20 were correlated with the ratio of helper T cells and suppressor T cells. Tear I-TAC, IL-8, CCL20, and TNF-α were significantly correlated with the ESSDAI of different domains. Conclusions Our results revealed that the ocular surface changes in pSS patients were significantly correlated with systemic hematologic indexes and disease activity.